Quasi-static free-boundary equilibrium of toroidal plasma with CEDRES++: Computational methods and applications. (June 2015) - Heumann, H.; Blum, J.; Boulbe, C.; Faugeras, B.; Selig, G.; Ané, J.-M.; Brémond, S.; Grandgirard, V.; Hertout, P.; Nardon, E.
<x content-type="archive" xml:space="preserve">Abstract</x> We present a comprehensive survey of various computational methods in CEDRES++ (Couplage Equilibre Diffusion Résistive pour l'Etude des Scénarios) for finding equilibria of toroidal plasma. Our focus is on free-boundary plasma equilibria, where either poloidal field coil currents or the temporal evolution of voltages in poloidal field circuit systems are given data. Centered around a piecewise linear finite element representation of the poloidal flux map, our approach allows in large parts the use of established numerical schemes. The coupling of a finite element method and a boundary element method gives consistent numerical solutions for equilibrium problems in unbounded domains. We formulate a new Newton method for the discretized nonlinear problem to tackle the various nonlinearities, including the free plasma boundary. The Newton method guarantees fast convergence and is the main building block for the inverse equilibrium problems that we can handle in CEDRES++ as well. The inverse problems aim at finding either poloidal field coil currents that ensure a desired shape and position of the plasma or at finding the evolution of the voltages in the poloidal field circuit systems that ensure a prescribed evolution of the plasma shape and position. We provide equilibrium simulations for the tokamaks ITER and WEST to illustrate the performance of CEDRES++ and its application areas.